Evaluation of platelet-rich plasma and fibrin matrix to assist in healing and repair of rotator cuff injuries: a systematic review and meta-analysis. (February 2017) - Fu, Chun-Jiang; Sun, Jia-Bing; Bi, Zheng-Gang; Wang, Xu-Ming; Yang, Cheng-Lin
Objective: To perform a meta-analysis examining the effectiveness of platelet-rich plasma and platelet-rich fibrin matrix for improving healing of rotator cuff injuries. Data sources/design: A meta-analysis of eligible studies was performed after searching Medline, Cochrane, and EMBASE on 14 December 2015. Setting: University hospital. Participants: Patients with rotator cuff injuries. Review methods/intervention: Databases were searched using the keywords "PRP or platelet-rich plasma, " "PRFM or platelet-rich fibrin matrix, " "rotator cuff, " and "platelet-rich" for studies comparing outcomes of patients with rotator cuff injuries that did and did not receive a platelet-rich product. Main measures: The primary outcome was a functional score change from pre- to post-treatment (Scorepost –Scorepre ). The secondary outcome was a visual analogue scale (VAS) pain score change from pre- to post-treatment (VASpost –VASpre ). Results: A total of 11 studies were included in the meta-analysis. The total number of patients that received platelet-rich plasma or platelet-rich fibrin matrix was 320 and the number of control patients was 318. The standard difference in means of the functional scores was similar between patients administered platelet-rich plasma/fibrin matrix and patients in the control group (standard difference in means for functional scores = 0.029; 95% confidence interval (CI): –0.132 to 0.190; p = 0.725). The standard difference in means was similar between patients administered platelet-rich plasma and the controls (standard difference in means = 0.142; 95% CI: –0.080 to 0.364; p = 0.209). Conclusion: The results of this meta-analysis do not support the use of platelet-rich plasma/platelet-rich fibrin matrix in patients with rotator cuff injuries.